COMPRESSION THERAPY EFFECTIVENESS IN VENOUS ULCERS HEALING: A LITERATURE REVIEW (Fiep Bulletin - online, 2013)
This is a study of literature review in order to check the databases Medline, Lilacs, Pub Med and HighWire Press, publications about the effectiveness of therapies in the treatment of compressive UVS. For this, they were used as descriptors the terms and effectiveness of varicose ulcer treatment, to the databases Medline and Lilacs and venous ulcer and compression therapy in PubMed and HighWire Press. The inclusion criteria used for selecting the items were work related to the effectiveness of Unna boots, or half of compression elastic bandage on the healing of UV; be presented in full text, available online, with free 346 access, and have been published from the year 2000. We selected 12 articles that addressed: the use of compression therapy (04 articles), the effectiveness of hydrocolloid associated with compression therapy compared the effectiveness of boots from Unna (02), the effectiveness of therapy and compression therapy of compression associated with surgery (2 ), The effectiveness of compression therapy of high compression and low compression (01), the accession and the comfort of compression therapy of 02 layers (01), the effectiveness of the inelastic and elastic compression (01), and the effectiveness of different therapies 08 compressive during rest, posture changes, exercise and after two days of use of therapy (01). In all studies was noted that the compression therapy is effective in healing of UVS and prevention of relapses, but no at this time, concrete information on what kind of compression therapy is more effective, being necessary to carrying out further clinical trials about this issue.
Keywords: Varicose ulcer; treatment effectiveness; compression therapy